Incidence of neonatal sepsis in relation to prolonged rupture of membranes (PROM)>18 hours and associated risk factors for early onset neonatal sepsis (EONS) - Dr. G. Kalyan Chakravarthi; Dr. S. Surya Veera Kumar (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: PROM is significant not only in perinatal morbidity and mortality, but also in the long-term neonatal complications and sequelae in survived neonates. The evaluation of neonatal sepsis is important so as to institute treatment as quickly as possible. Hence the present study is undertaken to determine the incidence of early onset neonatal sepsis in relation to PROM of more than 18 hours.Method: The present prospective study was conducted from December 2013 to November 2014 in GSL medical college and hospital, Rajahmundry. All the neonates born to mothers with history of prolonged rupture of membranes >18hrs during study period was formed sample size for present study. Institutional Ethical Clearance was obtained prior begin of the study. A detailed history was taken including age, parity, Obstetric history of the mother with emphasis on exact time of rupture of membranes, duration history and antibiotics before labour were evaluated.Result: The incidence of EONS in present study was found to be 14.5%. In present study the incidence of sepsis is higher in low birth weight neonates (66%) compared to normal birth weight babies (34%) and higher rate of incidence in preterm neonates (61.5%) than in term neonates (38.5%). Further, Staphylococcus aureus was the commonest isolate (45.45%) followed by CONS (27.27%).Conclusion: In conclusion, evaluation of neonatal sepsis is very important so as to institute treatment as quickly as possible.